2006
DOI: 10.1007/s00467-006-0238-8
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular mass and heart sympathetic activity after renal transplantation in children and young adults

Abstract: Recent studies considered that an increase in sympathetic activity (SA) may be responsible for left ventricular hypertrophy (LVH). Before and after renal transplantation (RT), we evaluated changes on left ventricular mass (LVM) and SA in 40 end-stage renal disease patients between 8 and 35 years old. Hypertension (95.0% vs. 71.0%; p=0.005), use of combined antihypertensive drugs (57.5% vs. 30.0%; p=0.01), and LVH (77.5% vs. 52.5%; p=0.01) significantly decreased after RT whereas low-to-high frequency ratio (LF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
(28 reference statements)
3
7
0
Order By: Relevance
“…We did not find any statistical difference in systolic blood pressure, and it was still high in Tx patients; however, diastolic blood pressure dropped close to the normal range in Tx patients, which might be explained by the better fluid status; although the intraindividual comparison showed no changes. The presence of LVH decreased in our observational study from 80% to 40%, and from almost 90% to 50% in the intraindividual comparison, which is in line with most of the former echocardiographic studies in children (6, 13, 14). In the cross‐sectional study, we did not find any patients with low LVEF after Tx and only one with high LVESVi.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We did not find any statistical difference in systolic blood pressure, and it was still high in Tx patients; however, diastolic blood pressure dropped close to the normal range in Tx patients, which might be explained by the better fluid status; although the intraindividual comparison showed no changes. The presence of LVH decreased in our observational study from 80% to 40%, and from almost 90% to 50% in the intraindividual comparison, which is in line with most of the former echocardiographic studies in children (6, 13, 14). In the cross‐sectional study, we did not find any patients with low LVEF after Tx and only one with high LVESVi.…”
Section: Discussionsupporting
confidence: 92%
“…Several reports have demonstrated that kidney Tx leads to the regression of LVH (6, 13, 14). However, these promising data were obtained by echocardiography which does not allow for accurate monitoring in patients on hemodialysis mainly due to the rapid changes in LV loading states (21) and further disadvantages of 2DE, such as limited access through the intercostal spaces (3), subjective interpretation, high interobserver variability, semiquantitative evaluation of regional systolic LV contraction and the need of geometric assumptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relation between LVM and a history of kidney transplantation [35], [36] and albumin [37] is in accordance with earlier literature.…”
Section: Discussionsupporting
confidence: 91%
“…Studies also have demonstrated that cardiac sympathetic activity is related to LVH in patients with primary [61] or CKDmediated hypertension [62].…”
Section: Altered Autonomic Control Of Cardiovascular Function In Ckdmentioning
confidence: 98%